Histological Structure of Male Wistar Rats’ Stomach Fed with Yam Tuber Flour Supplementation - Permana, Andre Dian; Kuntana, Yasmi Purnamasari; Malini, Desak Made (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2023)
A residential rat might harm human health because it acts as a disease reservoir. It has been many efforts to control this rate using synthetic rodenticide. Nevertheless, synthetic rodenticides broke the environment and made rats resistant. Yam (Dioscorea hispida) tube application on rat’s bite could solve the problem. This study evaluated the histology of male Wistar rats (Rattus norvegicus) fed with bite block supplemented with different yam tuber flour concertation to control residential rat populations. Five different treatments were applied with five replications. The treatments were negative control and brodifacoum 0.005% (positive control), 30%, 50%, and 70% of yam tuber flour. The results show that yam tuber supplementation caused damage to male Wistar rat stomachs, as indicated by mucosal erosion and the presence of inflammatory cells. The statistical test indicated that stomach damage significantly differed among treatments, with the severest damages caused by 50% yam tuber supplementation. It could be concluded that the rat’s bite containing yam tuber flour caused stomach damage, and the feed bite containing 70% yam tuber flour was the most effective. This result proved that yam tuber has good potential as a natural rodenticide to control residential rat populations.